Glucagon Reduces Neutrophil Migration and Increases Susceptibility to Sepsis in Diabetic Mice - Insuela, Daniella Bianchi Reis; Ferrero, Maximiliano Ruben; Gonçalves-de-Albuquerque, Cassiano Felippe; Chaves, Amanda da Silva; da Silva, Adriano Yagho Oliveira; Castro-Faria-Neto, Hugo Caire; Simões, Rafael Loureiro; Barja-Fidalgo, Thereza Christina; Silva, Patricia Machado Rodrigues e; Martins, Marco Aurélio; Silva, Adriana Ribeiro; Carvalho, Vinicius Frias (Frontiers in Immunology, 2021)
Sepsis is one of the most common comorbidities observed in diabetic patients, associated with a deficient innate immune response. Recently, we have shown that glucagon possesses anti-inflammatory properties. In this study, we investigated if hyperglucagonemia triggered by diabetes might reduce the migration of neutrophils, increasing sepsis susceptibility. 21 days after diabetes induction by intravenous injection of alloxan, we induced moderate sepsis in Swiss-Webster mice through cecum ligation and puncture (CLP). The glucagon receptor (GcgR) antagonist des-his1-[Glu9]-glucagon amide was injected intraperitoneally 24h and 1h before CLP. We also tested the effect of glucagon on CXCL1/KC-induced neutrophil migration to the peritoneal cavity in mice. Neutrophil chemotaxis in vitro was tested using transwell plates, and the expression of total PKA and phospho-PKA was evaluated by western blot. GcgR antagonist restored neutrophil migration, reduced CFU numbers in the peritoneal cavity, and improved survival rate of diabetic mice after CLP procedure, however, the treatment did no alter hyperglycemia, CXCL1/KC plasma levels, and blood neutrophilia. In addition, glucagon inhibited CXCL1/KC-induced neutrophil migration to the peritoneal cavity of non-diabetic mice. Glucagon also decreased the chemotaxis of neutrophils triggered by CXCL1/KC, PAF, or fMLP in vitro. The inhibitory action of glucagon occurred in parallel with the reduction of CXCL1/KC-induced actin polymerization in neutrophils in vitro, but not CD11a and CD11b translocation to cell surface. The suppressor effect of glucagon on CXCL1/KC-induced neutrophil chemotaxis in vitro was reversed by pre-treatment with GcgR antagonist and adenylyl cyclase or PKA inhibitors. Glucagon also increased PKA phosphorylation directly in neutrophils in vitro. Furthermore, glucagon impaired zymosan-A-induced ROS production by neutrophils in vitro. Human neutrophil chemotaxis and adherence to endothelial cells in vitro were inhibited by glucagon treatment. According to our results, this inhibition was independent of CD11a and CD11b translocation to neutrophil surface or neutrophil release of CXCL8/IL-8. Altogether, our results suggest that glucagon may be involved in the reduction of neutrophil migration and increased susceptibility to sepsis in diabetic mice. This work collaborates with better understanding of the increased susceptibility and worsening of sepsis in diabetics, which can contribute to the development of new effective therapeutic strategies for diabetic septic patients.